d - Reed, Peter W., 1944- 4 0 16; 5 (Australia : Thomson Nelson, 2006)
u
For late undergraduate students.
Includes bibliographical references and index.
Specialized.
Keywords: 2 -- 0; 6; Planning;Textbooks.;Management;Textbooks.;Study and teaching (Higher). -- Marketing;Marketing;Marketing; 20; 2